Ordinary organizations : why normal men carried out the Holocaust - Kühl, Stefan 1966- (Polity, 2016)
Beyond "ordinary men" and "ordinary Germans" -- Identification with the goal -- Coercion -- Comradeship -- Money -- The attractiveness of activities -- The generalization of motives -- From killers to perpetrators -- The normality and abnormality of organizations